2021
DOI: 10.1161/strokeaha.120.031769
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Acute Management and Outcomes During the COVID-19 Outbreak

Abstract: Background and Purpose: The coronavirus disease 2019 (COVID-19) outbreak has added challenges to providing quality acute stroke care due to the reallocation of stroke resources to COVID-19. Case series suggest that patients with COVID-19 have more severe strokes; however, no large series have compared stroke outcomes with contemporary non–COVID-19 patients. Purpose was to analyze the impact of COVID-19 pandemic in stroke care and to evaluate stroke outcomes according to the diagnosis of COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
4
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 31 publications
2
45
4
4
Order By: Relevance
“…The initial decrease in stroke presentations was followed by a rebound of 77% in the period May-June. The initial decrease in cases was like that reported in the literature (15,1722,2428,3439). We saw a reduction in stroke presentations despite a relatively low incidence of SARS-CoV-2 infections compared to other centres internationally.…”
Section: Discussionsupporting
confidence: 82%
“…The initial decrease in stroke presentations was followed by a rebound of 77% in the period May-June. The initial decrease in cases was like that reported in the literature (15,1722,2428,3439). We saw a reduction in stroke presentations despite a relatively low incidence of SARS-CoV-2 infections compared to other centres internationally.…”
Section: Discussionsupporting
confidence: 82%
“…To note, the incidence of COVID‐19 during the first wave might be underestimated since PCR tests were restricted to symptomatic patients, whilst the second wave also included asymptomatic PCR‐confirmed COVID‐19 patients. Interestingly, in contrast to the first wave [10], the rate of stroke admissions remained stable throughout the second wave.…”
Section: Resultsmentioning
confidence: 98%
“…One important concern related to the COVID-19 outbreak was its negative impact on acute stroke care, with reported reductions in ischaemic and hemorrhagic stroke hospitalizations, as well as in IVT and MT rates compared with historical controls [1,2]. A prior report from the Madrid Stroke Network analyzing the first COVID-19 pandemic wave showed a reduction in stroke admissions but a high rate of reperfusion therapies in patients with ischaemic stroke (43.3%), with no differences depending on COVID-19 diagnoses [10]. This finding, together with the maintenance of door-to-imaging, doorto-needle and door-to-puncture times within the recommended range, suggest that the solid organized framework helped address the COVID-19 pandemic without a major impact on acute stroke care [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…John and Kesav also reported that 15 out of 20 patients (75%) with COVID-19 and acute ischemic stroke had LVO ( 13 ). Also, SARS-CoV-2 positive stroke patients have been found to be younger, with a higher baseline NIHSS ( 14 ) and worse clinical outcomes ( 15 17 ), including increased mortality ( 18 ). These findings suggest that, besides the strain that the pandemic itself causes on health systems, stroke may be particularly aggravated.…”
Section: Introductionmentioning
confidence: 99%